A COMPARATIVE STUDY BETWEEN WESTERN AND ISLAMIC PERSPECTIVES ON HUMAN DEVELOPMENT AND LIFE-FRIENDLY ENVIRONMENT - Othman, Nooraini (Online Journal of Research in Islamic Studies, 2017)
Psychology and human development play a very important role in environmental sustainability. This article intends to highlight some of the important theories and concepts in order to develop understanding on the subject matter from these angles. The approach is comparative in nature. It seeks to understand the concepts and theories from the Western and Islamic perspectives. Human nature and human development as well as human personality form the important basis of this work. Finally, it is concluded with the aspect of human relationship with the environment.